The formation of the ore-bearing dolomite marble from the giant Bayan Obo REE-Nb-Fe deposit, Inner Mongolia: insights from micron-scale geochemical data - Chen, Wei; Liu, Hang-Yu; Lu, Jue; Jiang, Shao-Yong; Simonetti, Antonio; Xu, Cheng; Zhang, Wen (Mineralium deposita, 2020)
The genesis of Earth’s largest rare earth element (REE) deposit, Bayan Obo (China), has been intensely debated, in particular whether the host dolomite marble is of sedimentary or igneous origin. The protracted (Mesoproterozoic to Paleozoic) and intricate (magmatic to metasomatic) geological processes complicate geochemical interpretations. In this study, we present a comprehensive petrographic and in situ, high-spatial resolution Sr-Pb isotopic and geochemical investigation of the host dolomite from the Bayan Obo marble. Based on petrographic evidence, the dolomite marble is divided into three facies including coarse-grained (CM), fine-grained (FM), and heterogeneous marble (HM). All carbonates are ferroan dolomite with high SrO and MnO contents (> 0.15 wt.%), consistent with an igneous origin. Trace element compositions of these dolomites are highly variable both among and within individual samples, with CM dolomite displaying the strongest LREE enrichment. In situ 206 Pb/ 204 Pb and 207 Pb/ 204 Pb ratios of the dolomite are generally consistent with mantle values. However, initial 208 Pb/ 204 Pb ratios define a large range from 35.45 to 39.75, which may result from the incorporation of radiogenic Pb released from decomposition of monazite and/or bastnäsite during Early Paleozoic metasomatism. Moreover, in situ Sr isotope compositions of dolomite indicate a large range ( 87 Sr/ 86 Sr = 0.70292–0.71363). CM dolomite is characterized by a relatively consistent, unradiogenic Sr isotope composition ( 87 Sr/ 86 Sr = 0.70295–0.70314), which is typical for Mesoproterozoic mantle. The variation of 87 Sr/ 86 Sr ratios together with radiogenic 206 Pb/ 204 Pb signatures for dolomite within FM and HM possibly represents recrystallization during Early Paleozoic metasomatism with the contribution of radiogenic Sr and Pb from surrounding host rocks. Therefore, our in situ geochemical data support a Mesoproterozoic igneous origin for the ore-bearing dolomite marble in the Bayan Obo deposit, which subsequently underwent intensive metasomatism during the Early Paleozoic.